Intratemporal facial nerve neurofibroma: a case report and review of literature - H. Vijayendra; Yousef, Amro; Vijayendra, Vinay Kumar; Mahajan, Nilesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Facial nerve neurofibromas (FNN) are a rare benign tumor of facial nerve can arise from anywhere along the course of the facial nerve from the cerebellopontine angle (CPA) to the extracranial branches within the parotid. They are most commonly located in the parotid gland, and FNN in temporal bone are rarely reported. Intratemporal facial neurofibroma arise from facial nerve in internal auditory canal or in Fallopian canal. It usually manifests as progressive facial palsy, but also can present as sudden or repetitive facial palsy mimicking Bell’s palsy. We reported a case of intratemporal facial neurofibroma arising mainly from mastoid segment in 17-year-old female who presented with progressive facial palsy for 3 years. We briefly reviewed previous cases of intratemporal facial neurofibroma reported in the literature to provide a comprehensive understanding of this rare entity.